2013
DOI: 10.1111/appy.12057
|View full text |Cite
|
Sign up to set email alerts
|

Sexual abuse and substance abuse increase risk of suicidal behavior in Malaysian youth

Abstract: Introduction: The aim of this study was to determine the association between sexual abuse, substance abuse and socio-demographic factors with suicidal ideation (SI), plans (SP) and deliberate self-harm (DSH) and propose steps to prevent youth suicidal behavior. Methods: This was a cross-sectional study of 6786 adolescents aged 17-18 years, selected randomly from all Malaysian adolescents to undergo compulsory youth camps located in Selangor, Malaysia (2008Malaysia ( -2009). Participants were assessed using sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 17 publications
1
19
1
Order By: Relevance
“…This finding is similar with a study done by Arria et al, (2010) and Chan et al, (2013). Adolescents belonging to age group 13 to 17 years old with a history of sexual abuse were more likely to experience SI (56.37), CS (36.67) and DP (34.66).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is similar with a study done by Arria et al, (2010) and Chan et al, (2013). Adolescents belonging to age group 13 to 17 years old with a history of sexual abuse were more likely to experience SI (56.37), CS (36.67) and DP (34.66).…”
Section: Discussionsupporting
confidence: 92%
“…Study by Chan et al, (2013) showed that history of sexual abuse increased exponentially with age among Malaysian adolescents. Another study by S. Maria et al, (2010) showed respondents age 18 to 24 years old had history of sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a diagnosis of major depression, anxiety, substance use and epilepsy worsened risk for self-harm [12,24,25,[45][46][47][48]. Similarly in adolescents, precipitating factors for suicidal ideation included depression, anxiety, stress, substance use, being bullied, and being abused at home, either physically or verbally [26,49].…”
Section: Reported Motives For Suicide and Self-harmmentioning
confidence: 99%
“…However, most studies did not control for overlap with other high-risk factors, especially sociodemographic variables (such as social support, employment, alcohol use, and physical abuse; Maniglio, 2011b) that may coexist with childhood sexual abuse and increase the risk of suicide attempts. For example, one study of Malaysian youth found that childhood sexual abuse was a more important risk factor for suicide attempts than drinking alcohol (Chan et al, 2013). However, other sociodemographic factors were not taken into consideration in this study.…”
Section: Introductionmentioning
confidence: 99%